DEVELOPMENT OF WEBTOON APPLICATION-BASED MATH COMIC MEDIA (KOMIKA) IN LEARNING TO IMPROVE STUDENTS' NUMERACY LITERACY SKILLS: PENGEMBANGAN MEDIA KOMIK MATEMATIKA BERBASIS APLIKASI WEBTOON (KOMIKA) DALAM PEMBELAJARAN UNTUK MENINGKATKAN KEMAMPUAN LITERASI NUMERASI SISWA - Sutini; Wahyuni Fajar Arum; Rifka Anisa (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2024)
This research was conducted in response to the problems that seventh-grade students face in learning mathematics in the classroom, such as boredom and low achievement grades compared to the school's Minimum Completeness (KKM). The research aims to describe mathematics comic media's development process, validity, practicality, and effectiveness. The study was conducted at MTsN 2 Surabaya class VII G. The data collection techniques used were field notes, validation, response questionnaires, and test techniques. Furthermore, the research data obtained were analyzed using data analysis of field notes, validity, and practicality. Based on the results of the study, it was found that: (1) The process of developing math comics by using the Plomp development method. (2) The math comic media was declared